Triggering Receptor Expressed on Myeloid Cells 2 Protects Dopaminergic Neurons by Promoting Autophagy in the Inflammatory Pathogenesis of Parkinson’s Disease - Huang, Wei; Lv, Qiankun; Xiao, Yunfei; Zhong, Zhen; Hu, Binbin; Yan, Si; Yan, Yufang; Zhang, Junjun; Shi, Ting; Jiang, Lijuan; Li, Wen; Lu, Guohui (Frontiers in Neuroscience, 2021)
Parkinson’s disease is a neurodegenerative disorder with an inflammatory response as the core pathogenic mechanism. Previous human genetics findings support the view that the loss of TREM2 function will aggravate neurodegeneration, and TREM2 is one of the most highly expressed receptors in microglia. However, the role of TREM2 in the inflammatory mechanism of PD is not clear. In our study, it was found both in vivo and in vitro that the activation of microglia not only promoted the secretion of inflammatory factors but also decreased the level of TREM2 and inhibited the occurrence of autophagy. In contrast, an increase in the level of TREM2 decreased the expression of inflammatory factors and enhanced the level of autophagy through the p38 MAPK/mTOR pathway. Moreover, increased TREM2 expression significantly decreased the apoptosis of dopaminergic (DA) neurons and improved the motor ability of PD mice. In summary, TREM2 is an important link between the pathogenesis of PD and inflammation. Our study provides a new view for the mechanism of TREM2 in PD and reveals TREM2 as a potential therapeutic target for PD.